The Relationship Between Physical Activity and Suicidal Thought in Korean Adolescents - Taikyung Choi; Junghyun Kim (YCAB Publisher, 2026)
Background: The social changes of adolescence can cause stress in some adolescents, leading to increased rates of adolescent emotional disorders and suicide attempts, and serious public health problems such as suicide and self-harm. Existing studies on adolescent mental health have focused on the association between physical activity and depressive symptoms, but empirical studies examining the direct link with suicidal ideation are rare. Objectives: Therefore, this study aimed to investigate the independent and significant association between physical activity and suicidal ideation in Korean adolescents. Method: The sample was analyzed from the 20th (2024) Youth Health Behavior Survey of Korea. This study conducted a binary logistic regression analysis on 54.653 students from the first year of middle school to the third year of high school. Results: The prevalence of suicidal ideation was 12.7%, and suicidal ideation was found to increase with lower socioeconomic status (SES). The analysis of suicidal ideation related to physical activity revealed that the number of days of strength training performed in the past seven days was related to suicidal ideation. The odds ratio (OR) for those who performed strength training on three or more days was 1.11 (95% CI, 1.04-1.19) times higher than for those who performed it on two or fewer days. Conclusion: This study found that while general physical activity tended to be associated with lower suicidal ideation, frequent muscle-strengthening exercise was positively associated with suicidal ideation, suggesting that not all types of physical activity provide equal mental health benefits. Educational interventions should also aim to foster healthy motivation for physical activity by emphasizing self-efficacy rather than competition or appearance.